Study of the quality and integrity of spermatozoa acrosome caps in frozen sexing semen Friesian Holstein cattle - Sitiadira Aulia Aldini; Nurul Isnaini; Aulia Puspita Anugra Yekti; Trinil Susilawati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
Artificial insemination (AI) of dairy cows using sexing semen is the right choice to obtain female calves as replacement stock. The success of AI is influenced by the quality of the spermatozoa used. The purpose of this study was to determine the quality of semen produced by Lembang Artificial Insemination Center. The material used is 30 frozen semen straws of FH cattle produced by Lembang Artificial Insemination Center. This research method uses observational methods. The research variables included individual motility, viability, abnormalities, concentration, total motile spermatozoa, and intact acrosome caps of spermatozoa. The data obtained were analyzed by the Analysis of Variance (ANOVA) test and continued with Duncan's test if significantly different. The results showed that individual motility, concentration, total motile spermatozoa, and intact acrosome caps of spermatozoa had a very significant effect on all treatments (P<0.01), while spermatozoa abnormalities had a significant effect (P<0.05) on all treatments, but on viability, there was no effect (P> 0.05) in all treatments. Motility of individual spermatozoa in non-sexing semen (55.80±4.56)%, sperm X (46.30±5.36)%, sperm Y (46.70±6.40)%. Viability of spermatozoa in non-sexing semen (74.57±4.05)%, sperm X (73.24±2.30)%, sperm Y (72.51±2.68)%. Spermatozoa abnormalities in non-sexing semen (2.73±2.24)%, sperm X (4.94±1.57)%, sperm Y (3.25±2.72)%. Concentration of non-sexing semen (33.88±1.98 million/mini straw), sperm X (25.06±4.29 million/mini straw), sperm Y (25.13±5.74 million/mini straw). The number of sperm motile non-sexing (18.60±1.58 million/mini straw), sperm X (11.68±2.82 million/mini straw), sperm Y (25, 11.64±2.68 million/mini straw). Intact acrosome caps, non-sexing semen (78.40±4.84)%, sperm X (74.08±3.80)%, sperm Y (70.70±4.78)%.